Regional COVID-19 measures and effects on subjective well-being in Germany: observing trends over time with data from a large population survey - Finne, Emily; Nowak, Anna Christina; Razum, Oliver (Frontiers in Public Health, 2025)
BackgroundCOVID-19 measures in Germany varied during the pandemic, and it seems natural that in addition to factors such as incidence, health system capacity, etc., these interventions and their social and economic consequences had an impact on the evolution of the population’s well-being. Since the beginning of the pandemic, there has been a suspicion that the health burden would fall mainly on population groups with a lower socio-economic status, and that COVID-19, including the policy measures, could therefore contribute to increasing social inequalities in health. We examine several indicators of well-being over the course of the pandemic, analyze the effect of the stringency of the measures on subjective well-being and the extent to which certain social groups were particularly affected.MethodsOur analyses are based on 2020 and 2021 data from the German Socio-Economic Panel (SOEP), complemented by various regional indicators, including the COVID-19 measures. Data on subjective well-being during the pandemic phases were regressed on the phases, socio-demographic, economic and health-related indicators, stringency of measures and other regional indicators in multi-level models with the district as the top level. Up to N = 29,871 observations in 401 districts were included.ResultsOverall, there was little decline in well-being up to the end of the observation period, and even some increase. When the effect of the stringency of the measures was taken into account, the changes were partially attenuated. However, stringency had little direct effect on well-being. People with disabilities and chronic pre-existing conditions were particularly affected by a reduction in well-being. In some cases, COVID-19 measures had slightly different effects in these groups.ConclusionThe effects of socio-economic indicators were not strong enough to suggest that lower social status is generally associated with a negative trend in well-being. According to our results, people with disabilities and chronic diseases, including severe obesity, should be given more attention in the future. A change in time-related outcomes when considering COVID-19 measures could indicate adjustment effects on well-being.